Money Ethics And Tax Evasion - Merline Yulianti; Purwana Sari; Nasruji Nasruji (International Journal of Management Research and Economics, 2025)
This research aims to understand the influence of money ethics and tax morale on tax evasion. The population in this study is made up of taxable individuals registered in the KPP Pratama City of Batam, which amounts to 456,984 people. The sample technique used purposive sampling with 94 respondents. Data collection for this study uses the questionnaire method. The analysis method uses regression with the help of the SEM-PLS application version 4. Research findings show that money ethics has a significant positive influence on tax evasion, and tax morale has no significant effect on tax avoidance.